201k views
5 votes

3 + \frac{x - 3}{9 - {x}^(2) } / 3 - (4)/(x + 3)

3 + \frac{x - 3}{9 - {x}^(2) } / 3 - (4)/(x + 3)-example-1
User Ilmo Euro
by
7.5k points

1 Answer

0 votes


\frac{3 + \frac{x - 3}{9 - {x}^(2) } }{3 -(4)/(x + 3) } \\ = \frac{ \frac{3(9 - {x}^(2) ) + x - 3}{9 - {x}^(2) } }{ (3(x + 3) - 4)/(x + 3) } \\ = \frac{27 - 3 {x}^(2) + x - 3}{9 - {x}^(2) } * (x + 3)/(3x + 12 - 4) \\ = \frac{ - 3 {x}^(2) + x + 24 }{ - (x - 3)(x + 3)} * (x + 3)/(3x + 8) \\ = ( - (3x + 8)(x - 3))/( - (x - 3)) * (1)/(3x + 8) \\ = ( - (x - 3))/( - (x - 3)) \\ = 1

Hope this helps. - M
User Omikad
by
6.8k points